2013
DOI: 10.1051/0004-6361/201219725
|View full text |Cite
|
Sign up to set email alerts
|

Coronal heating by the partial relaxation of twisted loops

Abstract: Context. Relaxation theory offers a straightforward method for estimating the energy that is released when continual convective driving causes a magnetic field to become unstable. Thus, an upper limit to the heating caused by ensembles of nanoflaring coronal loops can be calculated and checked against the level of heating required to maintain observed coronal temperatures (T 10 6 K). Aims. We present new results obtained from nonlinear magnetohydrodynamic (MHD) simulations of idealised coronal loops. All of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 36 publications
7
53
0
Order By: Relevance
“…Only once the kink instability had led to the onset of a turbulent relaxation, did it become clear that the extent of the turbulent region would be about 1.8 times the diameter of the initial loop. It was suggested by Bareford et al [11] that, due to the presence of zero net vertical current, their relaxation region was more localized than previous simulations by Browning et al [9] in which turbulence filled the whole domain. However, our simulations with a net vertical current still have a localized turbulent region (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…Only once the kink instability had led to the onset of a turbulent relaxation, did it become clear that the extent of the turbulent region would be about 1.8 times the diameter of the initial loop. It was suggested by Bareford et al [11] that, due to the presence of zero net vertical current, their relaxation region was more localized than previous simulations by Browning et al [9] in which turbulence filled the whole domain. However, our simulations with a net vertical current still have a localized turbulent region (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…Another important difference is in the way Ohmic heating is handled. Bareford et al [17] found that regions of Ohmic heating appeared more or less at the same locations (and times) as shock heating, although the latter was far stronger than the former. By contrast, the use of a variable critical current employed here produces small pockets of Ohmic heating scattered near the footpoints and around the midplane.…”
Section: (C) Global Evolutionmentioning
confidence: 99%
“…The flux-rope field is purely toroidal (B z = 0) for this limiting value of λ. The threshold for the kink instability depends both on the specific transverse twist profile considered and on geometrical parameters such as the flux-rope aspect ratio (Bareford et al 2013). In our case, and for an aspect ratio L 0 /r 0 = 10, the kink instability is prone to develop for λ > ∼ 1.6.…”
Section: Model Dimensions and Parametersmentioning
confidence: 99%